Current Response in CaV1.3–/– Mouse Vestibular and Cochlear Hair Cells - Manca, Marco; Yen, Piece; Spaiardi, Paolo; Russo, Giancarlo; Giunta, Roberta; Johnson, Stuart L.; Marcotti, Walter; Masetto, Sergio (Frontiers in Neuroscience, 2021)
Signal transmission by sensory auditory and vestibular hair cells relies upon Ca2+-dependent exocytosis of glutamate. The Ca2+ current in mammalian inner ear hair cells is predominantly carried through CaV1.3 voltage-gated Ca2+ channels. However, while CaV1.3-/- mice are deaf, they do not show any obvious vestibular deficits, highlighting some possible differences in the way hair cells activate their postsynaptic afferent terminal between auditory and vestibular hair cells. Here, we investigated the Ca2+ current in CaV1.3-/- and wild-type mice to assess whether it was differently affected in the two sensory organs. Using 5 mM extracellular Ca2+ and near-body temperature conditions, we investigated the cochlear primary sensory receptors inner hair cells (IHCs) and both type I and type II hair cells of the semicircular canals. We found that the residual Ca2+ current in both auditory and vestibular hair cells from CaV1.3-/- mice was about 15% compared to controls, indicating a comparable expression of CaV1.3 Ca2+ channels in both sensory organs. We also showed that, different from IHCs, type I and type II hair cells from CaV1.3-/- mice were able to acquire the adult-like K+ current profile in their basolateral membrane. Finally, we found that the calyx-type afferent terminal of type I hair cells from CaV1.3-/- mice retained the ability to elicit depolarization-induced action potentials, suggesting the possibility that K+-based, non-exocytotic, afferent transmission is still functional in these mice. This non-vesicular mechanism is likely to underpin the apparent normal vestibular functions in CaV1.3-/- mice.